2006
DOI: 10.1029/2005gl025566
|View full text |Cite
|
Sign up to set email alerts
|

Co‐ and postseismic deformation of the 28 March 2005 Nias Mw 8.7 earthquake from continuous GPS data

Abstract: Global Positioning System (GPS) measurements registered up to >5m of coseismic displacements during the 28 March 2005 Mw = 8.7 Nias earthquake, Indonesia. The vertical offsets put tight constraints on the northern and southern limit of the rupture. The inferred coseismic slip distribution indicates high slip patches near the epicenter and near the southern extent of the 26 December 2004 Aceh‐Andaman rupture, where aftershocks have been abundant. Six months of postseismic time‐series are better fit with a logar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
51
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 16 publications
5
51
1
Order By: Relevance
“…The postseismic deformation observed at the Earth's surface commonly shows a rapid decrease in the absolute value of the rate of change with time; afterslip occurring at depth is also expected to show a similar behavior. It is shown in the above examples that patches of afterslip do not overlap much with those of coseismic fault slip and the afterslip generally adds a seismic moment that is 20 to 50% of the main shock [Melbourne et al, 2002;Yagi et al, 2003;Kreemer et al, 2006].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The postseismic deformation observed at the Earth's surface commonly shows a rapid decrease in the absolute value of the rate of change with time; afterslip occurring at depth is also expected to show a similar behavior. It is shown in the above examples that patches of afterslip do not overlap much with those of coseismic fault slip and the afterslip generally adds a seismic moment that is 20 to 50% of the main shock [Melbourne et al, 2002;Yagi et al, 2003;Kreemer et al, 2006].…”
Section: Introductionmentioning
confidence: 92%
“…Inversion analyses have shown that postseismic transients in the geodetic time series can be attributable largely to an afterslip process downdip from the coseismic rupture; we can mention the examples of the 1978 Miyagi-oki (M = 7.4) earthquake [Ueda et al, 2001], the 1997 Kronotsky (Mw = 7.8) earthquake [Bürgmann et al, 2002], the 1994 Sanrikuharuka-oki (Mw = 7.7) earthquake [Heki et al, 1997;Yagi et al, 2003], the 1995 Jalisco (Mw = 8.0) earthquake [Melbourne et al, 2002], the 2001 Peru (Mw = 8.4) earthquake [Melbourne et al, 2002] and the 2005 Nias (Mw = 8.7) earthquake [Kreemer et al, 2006]. However, there also exist a few examples indicating the occurrence of afterslip mostly updip from the coseismic rupture [Miyazaki et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…This logarithmic law is thus commonly used to fit afterslip displacements (e.g. Hsu et al 2006;Kreemer et al 2006;Freed 2007;Savage & Svarc 2009). In case long postseismic or preseismic data are available eqs (2) and (3) can be expanded with an additional linear term (at) representing the interseismic deformation.…”
mentioning
confidence: 99%
“…Figure 2 shows the postseismic transients in horizontal (east and north) components obtained from the GPS measurements taken in campaign mode during the period 2005-2008, and Table 1 gives the corresponding details of the observed data of postseismic velocity (ITRF2005) for these components. We discarded the first six months of data so as to avoid the postseismic relaxation contribution from poroelastic and afterslip mechanisms (Kreemer et al, 2006). We performed the exponential fitting for the time series ( Fig.…”
Section: Gps Data Collection and Modelingmentioning
confidence: 99%
“…The modeled and observed postseismic velocities are shown in Fig. 1b. 6 months of data so as to avoid the postseismic relaxation contribution from poroelastic and afterslip mechanisms (Kreemer et al, 2006). We performed the exponential fitting for the time series (Fig.…”
Section: Gps Data Collection and Modelingmentioning
confidence: 99%